Peran Humas dalam Pelayanan Pembelian Tiket Kereta Api Online (Studi di Stasiun Kepanjen Kabupaten Malang) - Samsul Hadi; Kukuh Sinduwiatmo (Kanal: Jurnal Ilmu Komunikasi, 2016)
This study aimed to describe the role of Public Relations PT. KAI Daerah Operasi 8 Surabaya was conducted by Head of Kepanjen Station in purchasing train tickets online at Kepanjen Station. This research used qualitative descriptive research. Primary data sources were collected directly from respondents by interview that will be submitted Public Relations Manager of DAOP 8 Surabaya, Head of Kepanjen Station, and buyer train tickets at Kepanjen Station. The results showed that the Head of Station Kepanjen Station had implemented four categories of public relations roles ie communication technician, expert prescriber, communication facilitator, and problem-solving facilitator well.